Leadership in world society: power and change from the perspective of sociological institutionalism - Jakobi, Anja P. (2011)
Abstract: The idea of a world society has become more frequent in contemporary analyses of International Relations (IR) scholarship, in particular from the perspective of sociological institutionalism. While such studies often examine questions of norms and legitimacy, this paper argues for a broader conceptualization of sociological institutionalism. Power and change are also elements of this framework and can be used for a variety of analyses in IR. To show this link, Anja P. Jakobi first presents the background of sociological institutionalism, elaborating both on the idea of world society as well as on organizational analyses in her working paper. In a second step, she brings together this broader understanding of world society with world politics. In a third step, she shows how power and change can be conceptualized, drawing on the idea of institutional entrepreneurship developed in organization studies. In the fourth step, she illustrates her theoretical claims with a presentation of g